2022
DOI: 10.1177/11786329221141829
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Best Practices in Disclosing a Dementia Diagnosis: A Clinician Interview Study

Abstract: The vast majority of individuals with dementia want to receive a diagnosis. Research suggests, however, that only a fraction of individuals with dementia receive a diagnosis and patients and families often feel the information is poorly explained. We thus aimed to assess clinician-reported barriers to dementia disclosure and recommendations for giving a dementia diagnosis. To accomplish this, we performed telephone interviews with 15 clinicians from different specialties using a semi-structured interview guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, follow up visits can re-orient PLWD/caregivers to information, as it is likely they will not remember all information during disclosure [ 18 , 24 , 25 ]. However, systems-level barriers like clinical schedules/short visits and follow up appointment availability can make this challenging [ 47 ]. One way to supplement clinician education is to provide materials to increase knowledge about dementia [ 48 ], support decision-making, and improve satisfaction and medication compliance (e.g., question prompt lists, decision aids) [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, follow up visits can re-orient PLWD/caregivers to information, as it is likely they will not remember all information during disclosure [ 18 , 24 , 25 ]. However, systems-level barriers like clinical schedules/short visits and follow up appointment availability can make this challenging [ 47 ]. One way to supplement clinician education is to provide materials to increase knowledge about dementia [ 48 ], support decision-making, and improve satisfaction and medication compliance (e.g., question prompt lists, decision aids) [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that clinicians should also tailor communication to patient preferences, such as spending alone-time with the patient before diagnostic communication and/or progressively disclosing a dementia diagnosis or information 18 . Some of these recommendations for optimal triadic communication overlap with recommendations for triadic communication in healthcare encounters generally, such as involving family members/caregivers in the conversation, building rapport, and meeting emotional and information needs 34,67 . However, other recommendations for communication in dementia settings are more tailored to individuals with cognitive impairment, such as using short sentences and visual aids 25 …”
Section: Discussionmentioning
confidence: 99%
“…• Communication about EOL care between professional caregivers and nursing home residents was uncommon; Communication about EOL care between professional caregivers and relatives was more frequent The diagnosis should be given in understandable language (Gruters, 2021) 22 Retain information and reduce uncertainty (Gruters, 2021) 22 Use a patient-centered approach to sensitively deliver the diagnosis (Phillips 2012) 27 Sensitively deliver the diagnosis (Phillips 2012) 27 Strategies to disclose the diagnosis may include avoiding elaboration, confirming comprehension, and using explicit terminology (Karnieli-Miller, 2007) 24 Lessen the impact of receiving bad news (Karnieli-Miller, 2007) 24 Check patient understanding and communicate empathically (Wollney 2020b) 35 Reflect patient preferences and education needs (Wollney 2020b) 35 Tailor communication to patient and caregiver preferences, backgrounds, and understanding of dementia (Wollney 2020a; Lecouturier, 2008) 25,34 Effectively deliver the diagnosis and educate patients and caregivers (Wollney 2020a; Lecouturier, 2008) 25,34 Caregivers sometimes thought that use of words like "dementia" or "Alzheimer" to disclose the diagnosis overshadowed subsequent information for patients (Byszewski, 2007) 18 Increase patient understanding of the diagnosis (Byszewski, 2007) 18 Involve a family member Patients agreed that a caregiver (family members or non-familial, e.g., neighbor or friend) should be present (Byszewski, 2007; Forbes, 2013) 18,39 Provide the patient with support (Byszewski, 2007; Forbes, 2013) 18,39 Family members present during the diagnosis may be able to adapt their behavior to the patient (Gruters, 2021) 22 Reflect understanding of patients' dementia-related behaviors (Gruters, 2021) 22 Align patient, family, and clinician perspectives about the presence of cognitive impairment (Aufill, 2019) 38 Move toward detection and diagnosis of cognitive impairment (Aufill, 2019) 38 Use a family-centered approach and acknowledge caregivers' roles and needs (Griffin, 2020) 43 Assess caregiver unmet needs, burden, and capacity to provide care (Griffin, 2020) 43 Provide opportunities for caregivers to have sep...…”
Section: Congruencementioning
confidence: 99%
See 1 more Smart Citation